Accurate and fast speckle interferometry in severe illumination conditions. (July 2022) - Zhang, Tao; Ye, Yimin; Zhang, Shuiqiang; Su, Zhilong; Zhang, Dongsheng
Highlights: The innovative method facilitates the use of speckle interferometry in severe conditions where uniform illumination cannot be achieved. An effective speckle image fusion scheme has been proposed to achieve to expand the dynamic range of the camera. A heterogeneous concurrency computing is employed to achieve real-time phase shifting. The proposed method is validated with both simulation and experimental studies. Abstract: Illumination conditions are an important factor affecting the accuracy of speckle interferometry. High-intensity illumination could cause the speckle images to be overexposed due to the limited dynamic range of the camera, degrading the fringe quality. This study proposes a high-dynamic phase reconstruction method enabling accurate speckle interferometry by means of speckle image fusion. Integrating with phase shifting, a real-time and robust speckle interferometric measurement routine is established by using a heterogeneous concurrency computing. To show the performance, the proposed method is exemplarily applied to shearography with both simulation and experimental studies. Results suggest that the proposed image fusion scheme is effective in dealing with the non-uniform illumination. The proposed linear fusion operator is accordance with the requirement of phase extraction for temporal phase shifting by balancing the image quality and computational efficiency. The innovative method facilitates the use of speckle interferometry in severe conditions where uniform illumination cannot be achieved due to surface conditions.